IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF DIFFERENTIATED LEARNING IN A PROBLEM-BASED LEARNING MODEL - Yunisa Aulia; Dadang Dahlan; Hana Mardiati Dahlan (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
The aim of this research is to determine the extent to which students' learning outcomes have improved through the application of differentiated learning in a Problem-Based Learning (PBL) model in the Economics subject. The study employs a action research, consisting of two cycles, beginning with a pre-cycle. Each cycle includes the stages of planning, implementing, observing, and reflecting. The results of the research indicate an improvement in students' affective learning outcomes, with pre-cycle data showing 85% (good category), Cycle I showing 82% (good category), and Cycle II showing 88% (very good category). Psychomotor learning outcomes also showed an increase, starting from 78% in the pre-cycle (good category), rising to 82% in Cycle I (good category), and reaching 86% in Cycle II (very good category). Cognitive learning outcomes demonstrated significant improvement as well, with pre-cycle average scores at 57 (10 students achieving the passing grade, 28%), Cycle I average scores at 77 (26 students achieving the passing grade, 72%), and Cycle II average scores at 86 (31 students achieving the passing grade, 86%). The research demonstrates that the implementation of differentiated learning within a Problem-Based Learning model effectively enhances student learning outcomes in the Economics subject.